Exploring the Relationship Between Corporate Social Responsibility, Trust, Corporate Reputation, and Brand Equity - Zhao, Yan; Abbas, Manzir; Samma, Madeeha; Ozkut, Tarik; Munir, Mubbasher; Rasool, Samma Faiz (Frontiers in Psychology, 2021)
The purpose of this study is to investigate the relationship between corporate social responsibility (CSR), corporate reputation (CR), and brand equity (BE). Building on the resource-based theory of the firm, this study proposes a theoretical framework. In this framework, CSR is theorized to strengthen CR and brand equity, directly and indirectly, through consumer trust. We used a questionnaire survey approach. In the questionnaire, 17 items were used with a 5-point Likert-Scale (1 stands for “strongly disagree,” and 5 stands for “strongly agree”). Data were collected from the consumers of the banking sector in the vicinity of Lahore, Pakistan. To estimate the proposed relationships in the conceptual model, we use structural equation modeling (SEM) through Smart PLS 3.2. The outcomes of this study confirm that CSR significantly impacts CR and brand equity. It is also demonstrated that trust mediates positively and significantly in the relationship between CSR, CR, and BE. Results of the present study have several implications for the senior management, marketing expert, administrators, and policymakers. This study expresses how CSR boosts BE and CR. Moreover, this study also indicates that trust is an important factor that enhances BE and CR.